Origins and diversity of a cosmopolitan fern genus on an island archipelago - Wolf, Paul G. (AoB Plants, 2015)
Isolated oceanic islands are characterized by patterns of biological diversity different from that on nearby continental mainlands. Isolation can provide the opportunity for evolutionary divergence, but also set the stage for hybridization between related taxa arriving from different sources. Ferns disperse by haploid spores, which are produced in large numbers and can travel long distances in air currents, enabling these plants to become established on most oceanic islands. Here, we examine the origins and patterns of diversity of the cosmopolitan fern genus Pteridium (Dennstaedtiaceae; bracken) on the Galapagos Islands. We use nucleotide sequences from two plastid genes, and two nuclear gene markers, to examine phylogeography of Pteridium on the Galapagos Islands. We incorporate data from a previous study to provide a worldwide context. We also sampled new specimens from South and Central America. We used flow cytometry to estimate genome size of some accessions. We found that both plastid and nuclear haplotypes fall into two distinct clades, consistent with a two-diploid-species taxonomy of P. aquilinum and P. esculentum. As predicted, the allotetraploid P. caudatum possesses nuclear haplotypes from both diploid species. Samples from the Galapagos include P. esculentum subsp. arachnoideum, P. caudatum and possible hybrids between them. Multiple Pteridium taxa were also observed growing together at some sites. We find evidence for multiple origins of Pteridium on the Galapagos Islands and multiple origins of tetraploid P. caudatum throughout its range in Central and South America. We also posit that P. caudatum may include recent diploid hybrids, backcrosses to P. esculentum, as well as allotetraploid plants. The Galapagos Islands are positioned close to the equator where they can receive dispersing propagules from both hemispheres. This may partly explain the high levels of diversity found for this cosmopolitan fern on these islands.